Determinação dos modos de vibração e do índice de refração não-linear dos compostos RECOB - Oliveira, Glaydson Francisco Barros de (2008)
In this work we present the room-temperature phonon spectra of the rare-earth calcium oxyborates [RECa4O(BO3)3, RE=La and Gd] obtained using Raman scattering technique. The observed frequencies were assigned on the basis of the borate (BO3) vibrations and correlations with previous data reported for other similar compounds. The influence of the RE ion substitution on the phonon distribution is discussed. Two main features were observed when La3+ replaces for Gd3+: the frequency of most of the phonons shifts downwards and the frequency difference between the components of the 1(BO3) doublet decreases. All these features result from the monoclinic lattice expansion. We also present the z-scan characterization of the nonlinear refractive indices (n2) of these compounds, which are new promising Yb-doped laser hosts. High values of the nonlinear refractive indices indicate the possibility of substantial Kerr-lensing and selfphase modulation effects in femtosecond oscillators and amplifiers